Binomial Parameter Estimation: Asymptotic analysis of Normality and Confidence Regions Using Moments Estimators - Salma Saad,; Kamilah Othman,; Naeima Abdelati, (AlQalam Journal of Medical and Applied Sciences, 2025)
Confidence regions for binomial distributions are widely used in practical research. Extensive application has interested many statisticians in improving new methods for constructing these regions in asymptotic and exact ways. This research primarily aims to construct confidence ellipses for parameters p and m of the binomial distribution Bin(m,p) using a sample of fixed size n in the method of moments estimators. Although the conventional method of moments estimators for p and m are well-established and straightforward to derive, their denominators can reach zero with positive probabilities. This study introduces modified estimators to effectively address this issue. By using the asymptotic normality of the joint distribution of both the conventional and modified estimators, we examine the quadratic forms of these estimators that follow a chi-square distribution, enabling the construction of simultaneous confidence regions (ellipses) for the parameters p and m. The method of moments estimators for binomial parameters p and m are found to be approximately normal, which allows for confidence regions to be constructed based on the chi-square distribution. Presenting modified estimators to handle zero-denominator issues ensures robust and reliable inferences. The theoretical side of the confidence region results show the effectiveness of binomial parameters p and m using modified estimators, solving the limitations of conventional approaches. This method provides a powerful framework for statistical inference, relying on asymptotic normality and a chi-square distribution. This method provides a powerful framework for statistical inference because it depends on asymptotic normality and the chi-square distribution. تُستخدم مناطق الثقة للتوزيعات ثنائية الحدين على نطاق واسع في البحث العملي. وقد أثار التطبيق الواسع اهتمام العديد من الإحصائيين بتحسين الأساليب الجديدة لبناء هذه المناطق بطرق مقاربة ودقيقة. يهدف هذا البحث في المقام الأول إلى بناء نقاط بيضاوية للثقة للمعلمات p و m للتوزيع ثنائي الحدين Bin(m,p) باستخدام عينة ذات حجم ثابت n في طريقة تقديرات العزوم. على الرغم من أن الطريقة التقليدية لتقديرات العزوم لـ p و m راسخة ومباشرة في الاستنباط، إلا أن مقاماتها يمكن أن تصل إلى الصفر باحتمالات موجبة. تقدم هذه الدراسة تقديرات معدلة لمعالجة هذه المشكلة بشكل فعال. من خلال استخدام التوزيع الطبيعي المقارب للتوزيع المشترك لكل من التقديرات التقليدية والمعدلة، نفحص الأشكال التربيعية لهذه التقديرات التي تتبع توزيع مربع كاي، مما يتيح بناء مناطق ثقة متزامنة (نقاط بيضاوية) للمعلمات p و m. لقد تبين أن طريقة تقدير اللحظات للمعاملات الثنائية p و m طبيعية تقريبًا، مما يسمح بإنشاء مناطق ثقة بناءً على توزيع مربع كاي. إن تقديم مقدرين معدلين للتعامل مع مشكلات المقام الصفري يضمن استدلالات قوية وموثوقة. يُظهر الجانب النظري لنتائج منطقة الثقة فعالية المعاملين الثنائيين p و m باستخدام مقدرين معدلين، وحل قيود الأساليب التقليدية. توفر هذه الطريقة إطارًا قويًا للاستدلال الإحصائي، بالاعتماد على التوزيع الطبيعي المقارب وتوزيع مربع كاي. توفر هذه الطريقة إطارًا قويًا للاستدلال الإحصائي لأنها تعتمد على التوزيع الطبيعي المقارب وتوزيع مربع كاي